Improving the Students’ Skill of Writing Narrative Text through Cooperative Learning Model with Jigsaw Technique - Siti Rodhia Harahap; Muchlas Suseno; Riana Bagaskorowati (Journal of English Language Studies, 2019)
The purpose of this action research are: 1) Describe the learning process of writing narrative text through cooperative model learning with jigsaw technique, 2) Describe the improvement of writing narrative text through cooperative model learning with jigsaw technique. The research design of this research is action research which use two cycles. Data in this research are qualitative and quantitative data. Qualitative data were obtained from observation sheets, daily observation journals, as well as documentation. Quantitative data is data in the form of numbers from the results of writing tests obtained after the learning process with cooperative model learning with jigsaw technique. While the data sources in this study are sixth graders SD Negeri 01 Tugu Utara Jakarta Utara year 2018-2019. The results showed that 1) the activities of learners in the learning process increased significantly after following the learning by using cooperative model learning with jigsaw technique, the result show 82.0 in the first cycle and 89.3 in the second cycle for activities the learner in the learning process, 2) Students' skills of writing narrative increased significantly after following the learning by using cooperative model learning with jigsaw technique. The average value obtained by learners are; cycle I is 74.18, and cycle II is 83.00.